ESTABLISHMENT OF MUSIC CLUBS IN SECONDARY SCHOOLS - Mirodil Khakimov (Journals Park Publishing, 2022)
This article is intended for artistic and pedagogical purposes, the organization of the singing ensemble and the organization of classes, taking into account the internal conditions of the school, the individual characteristics, interests and needs of students in the successful operation of the ensemble.
Keywords: National music; music club; talent